Organizacionno-metodiceskie aspekty upravlenija professional'nym basketbol'nym klubom (na primere PBK CSKA) - Kuscenko, S. V.; Kostikova, L. V. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The purpose of the research was the generalization of the experience and the perfection of organizational, sports and economic activities of professional basketball club of Russia (on the example of CSKA, Moscow). The authors have assumed, that the successful decision of high sports tasks facing the professional basketball club, can be provided with a choice of an essentially new, more effective model of the organization of its economic activities appropriate to the modern conditions.